2012
DOI: 10.1177/0022022112470749
|View full text |Cite
|
Sign up to set email alerts
|

Acculturation of Personality

Abstract: The present study tests the hypothesis that involvement with a new culture instigates changes in personality of immigrants that result in (a) better fit with the norms of the culture of destination and (b) reduced fit with the norms of the culture of origin. Participants were 40 Japanese first-generation immigrants to the United States, 57 Japanese monoculturals, and 60 U.S. monoculturals. All participants completed the Jackson Personality Inventory (JPI) as a measure of the Big Five; immigrants completed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 55 publications
2
24
0
2
Order By: Relevance
“…All the path coefficients of validation model were good fit for the data (in Table 2 ). These results supported the view that personality traits and spiritual beliefs can be subject to cultural influence [ 79 ] and predict on resilience [ 47 , 80 ].…”
Section: Discussionsupporting
confidence: 84%
“…All the path coefficients of validation model were good fit for the data (in Table 2 ). These results supported the view that personality traits and spiritual beliefs can be subject to cultural influence [ 79 ] and predict on resilience [ 47 , 80 ].…”
Section: Discussionsupporting
confidence: 84%
“…Normative personality profiles on the Big Five contrast in Japanese and European Americans (Bornstein et al, 2007). An examination of personality concordance in Japanese American immigrants with mainstream groups in Japan and the United States revealed that greater involvement in the mainstream European American culture changed personality in Japanese immigrants (Güngör, Bornstein, De Leersnyder, Cote, Ceulemans, & Mesquita, 2013). …”
Section: Specificity Principle: Peoplementioning
confidence: 99%
“…Furthermore, they appear to be highly consistent. Similar effects of familiarity can be seen in other facets of acculturation such as personality (Eap et al, 2008;Güngör et al, 2013) and self-concept (Heine & Lehman, 2004). Investigating these mechanisms in the socially relevant construct of mental state reading can contribute significantly to understanding the impact of intercultural contact, especially when the focus is on groups other than the often-investigated Asian and Western ones.…”
mentioning
confidence: 57%